THE PROBLEM OF EXAMINATION OF CORPORATE DISPUTE CASE WITHIN A REASONABLE TIME IN RA CIVIL LITIGATION - Baghdasaryan, Larisa (State and Law, 2023)
As a result of the investigation, it was found out that there are some restrictions regarding the examination of certain cases of corporate disputes, both in the case of simplified and expedited proceedings, on the basis of which there is a problem of maintaining a corporate dispute case within a reasonable time. Regarding the solution of the mentioned legal problem, there has been made a proposal, which will give an opportunity to the court to apply an expedited trial and reject the claim, saving both the court costs of the persons involved in the case, as well as to relieve the court from unnecessary examination of a number of cases in which there is a misuse of the realization of procedural rights by the involved person in the case.
Keywords: Corporate legal relations; corporate disputes; the right to hear a case within a reasonable time; expedited proceedings; misuse of law; inappropriate claimant